2007
DOI: 10.2353/ajpath.2007.061258
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Activation of Signal Transducer and Activator of Transcription-5B Signaling in the Vessel Wall Reduces Balloon Injury-Induced Neointima Formation

Abstract: Previously, we have demonstrated that STAT-5B plays a role in thrombin-induced vascular smooth muscle cell (VSMC) growth and motility. To learn more about the role of STAT-5B in vessel wall remodeling, we examined its involvement in platelet-derived growth factor-BB (PDGF-BB)-stimulated VSMC growth and motility and balloon injury-induced neointima formation. PDGF-BB activated STAT-5B as measured by its tyrosine phosphorylation, DNA binding, and reporter gene activity. PDGF-BB induced cyclin D1 expression, CDK4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…2A regulation, cyclin D1 has been reported to play a role in cell migration (32). In this aspect, we recently reported that STAT-5B-dependent expression of cyclin D1 plays a role in PDGF-BBinduced VSMC migration (24,33). Because NFATc1 plays a role in PDGF-BB-induced HASMC DNA synthesis and migration, and it mediates PDGF-BB-induced cyclin D1 expression, we were intrigued to find whether cyclin D1 has any role in HASMC migration downstream of NFATc1.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2A regulation, cyclin D1 has been reported to play a role in cell migration (32). In this aspect, we recently reported that STAT-5B-dependent expression of cyclin D1 plays a role in PDGF-BBinduced VSMC migration (24,33). Because NFATc1 plays a role in PDGF-BB-induced HASMC DNA synthesis and migration, and it mediates PDGF-BB-induced cyclin D1 expression, we were intrigued to find whether cyclin D1 has any role in HASMC migration downstream of NFATc1.…”
Section: Resultsmentioning
confidence: 97%
“…CDK4 Assay-Protein extracts from cells or tissues were analyzed for CDK4 activity as described previously (24). The 32 Plabeled Rb protein was visualized by autoradiography, and the band intensities were quantified using NIH Image J.…”
Section: Reagents-cyclosporinmentioning
confidence: 99%
“…CDK4/6 and Pak1 Assays-Cell extracts were analyzed for CDK4/6 and/or Pak1 activities as described previously (26,27). The […”
Section: Methodsmentioning
confidence: 99%
“…DNA Synthesis-DNA synthesis was measured by [ 3 H]thymidine incorporation as described previously and expressed as counts/min/dish (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation